Pengaruh Terapi Kelompok Terapeutik Terhadap Kemampuan Keluarga dalam Memberikan Stimulasi Perkembangan Rasa Percaya Usia Bayi di Kelurahan Batu Ampar Kramatjati Jakarta Timur Tahun 2010 - Damayanti, Rika (Universitas Islam Negeri Raden Intan Lampung, 2014)
The aim of this research her to get comprehensive picture about the influence therapeutic group therapy to family’s ability stimulating for infant, and infant development trust in district of Batu Ampar, Kramatjati Jakarta Timur. Design research is “Quasi experimental design with pre post test approach on intervention and kontrol group.